2012
DOI: 10.4103/0019-5278.107072
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status of workers of building construction industry

Abstract: Background:Informal/unorganised sector covers 92% of the total work force in India. About 50% of the construction industrial workers belonged to informal/unorganised sector.Material and Methods:The present study was undertaken to know the socio-economic status of construction worker and availing of the social security measures by this working group.Results and Conclusion:The study covered 150 subjects with an average age of 32 years and mean duration of work was nine years. They were poorly paid with an averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 7 publications
3
15
0
1
Order By: Relevance
“…Reduced prices of fruits and vegetables lead to increased rates of consumption of these foods (Waterlander et al, 2013). The result that wages influence nutritional intake also corroborates with findings from Tiwary et al (2012), which reported that fruits and vegetable consumption among construction workers was rare, primarily due to the low wages they were paid. The studies by Du Plessis (2011,2012) also corroborate that wages, availability of foods, and cultural background including cultural beliefs and gender-based distinctions have influence on intake of fruits and vegetables among construction workers.…”
Section: Discussionsupporting
confidence: 81%
“…Reduced prices of fruits and vegetables lead to increased rates of consumption of these foods (Waterlander et al, 2013). The result that wages influence nutritional intake also corroborates with findings from Tiwary et al (2012), which reported that fruits and vegetable consumption among construction workers was rare, primarily due to the low wages they were paid. The studies by Du Plessis (2011,2012) also corroborate that wages, availability of foods, and cultural background including cultural beliefs and gender-based distinctions have influence on intake of fruits and vegetables among construction workers.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with the observation that migrant construction workers, in their destination countries, frequently accept precarious employment conditions and perform risky tasks to work . In the case of Argentina, construction is one of the sectors with the most deregulation and labor flexibility, and in which the most migrants are used .…”
Section: Discussionsupporting
confidence: 88%
“…In addition, sociodemographics differed substantially. As in other studies, migrant workers were younger than local workers and most of them only had some form of primary education, while at least some of the local construction workers had received a secondary education. Many jobs on the construction site only require a low level of education, which is associated with simpler and potentially more hazardous jobs in this industry.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…49.29%, similar study done by Tiwary and Gangopadhyay et al in India in which average age was 32 years out of 150 study subjects. 12 In our study majority 41.43% of subjects were educated up to primary school and 22.14% were illiterate, the study done by Tiwary et al literacy rate was 79% of the subjects and 10% of subjects have passed class X examination. 12 In a study by Shah and Mehta, 20% were illiterate and did primary education were 42.08%.…”
Section: Discussionmentioning
confidence: 42%